A study of anemia in hypothyroidism with reference to vitamin B12 deficiency - Bhuta, Palak; Shah, Amit; Muley, Arti (International Journal of Advances in Medicine, 2019)
Background: Hypothyroidism is the most common of thyroid disorders in India. Anemia and hypothyroidism often occur simultaneously. Only few studies have assessed the role of vitamin B12 deficiency in this anemia. So, we planned this study to assess prevalence of anemia in hypothyroidism and to see if there is any association between vitamin B12 deficiency and anemia in these patients. Methods: It was an observational study. All hypothyroid patients attending the medicine OPD or admitted to medicine wards were enrolled for the study. Total 60 patients were included. Data was analyzed to assess the burden of anemia and B12 deficiency in hypothyroid and to find out any correlation between TSH level, anemia and vitamin B12 deficiency.). Results: About one third of hypothyroid had decreased vitamin B 12 levels. TSH level showed significant positive correlation with hemoglobin value. 28% of the hypothyroid patients had vitamin b12 deficiency, but TSH levels itself did not correlate with vitamin B12 level. However, it was seen that those who had combined thyroid and B12 deficiency had significantly higher chances of developing generalized swelling and breathlessness. Conclusions: Although there is no correlation between TSH level and B12 deficiency, it may be helpful to determine B12 level in hypothyroid patients who present with anemia, generalized swelling and/or breathlessness as B12 supplementation may give better symptomatic relief in them as compared to treating with thyroxine alone. More elaborative studies with larger sample size are required to explore this rather unattended relation of anemia in hypothyroidism with B12 deficiency.